Pengaruh Kecanduan Internet Dan Karakter Remaja Religius Terhadap Kualitas Keluarga - Hartanto, Dody; Fauziah, Mufied (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this study was to determine the effect of internet addiction on family quality through the character of adolescent religiosity. This research is quantitative research using explanatory survey method. There are 2 independent variables and 1 dependent variable, where the independent variable is globalization and adolescent religious character while the dependent variable is family quality. The research was conducted in 8 sub-districts in the city of Yogyakarta. The research subjects were adolescents under 24 years of age for men and 21 years for women who were married. The number of research subjects 156 respondents. The data collection technique used a scale of internet addiction, religiosity, and family quality. The data analysis technique used is path analysis using SPSS 23.00 for window. The results showed that globalization contributed positively to religiosity by 0.125. However, globalization does not have a direct influence on the quality of the family. While the religiosity variable contributed positively to the quality of the family by 0.251. Therefore, through this research it is known that globalization has an indirect effect on family quality through religiosity of 0.031.